Always affecting the wrong people? The impact of US sanctions on poverty - Matthias Neuenkirch; Florian Neumeier (Philipps-University Marburg, Faculty of Business Administration and Economics, 2015)
In this paper, we analyze the effect of US economic sanctions on the target countries' poverty gap during the period 1978 - 2011. Econometrically, we employ a nearest neighbor matching approach to account for differences in the countries' economic and political environment and the likelihood of being exposed to US sanctions. Our results indicate that US sanctions are indeed affecting the wrong people as we observe a 2.3 - 5.1 percentage points (pp) larger poverty gap in sanctioned countries compared to their nearest neighbors. Severe sanctions, such as fuel embargoes, trade restrictions, the freezing of assets, or embargoes on most or all economic activity are particularly detrimental and lead to an increase in the poverty gap by 6.1 - 7.4 pp.
Keywords: F51; F52; F63; I32; 330; Economic Sanctions; Nearest Neighbor Matching; Poverty; United States